Design of an Auto-pointing System for a Geostationary Earth Orbit Application - Jarnestål, Eric; Staf, Staffan (My University, 2023)
This report documents a masters thesis in which a systematic product development process was applied to create an auto-pointing subsystem for a satellite internet user terminal. The current product of Satcube AB is a manually operated termi nal, hence the need for an automated alternative. The aim of the project was to explore the undiscovered solution space of minimally actuated, automated antenna pointers. The sub-system should only utilise two actuators for the antenna’s three axes of rotation requiring a state-of-the art design. Furthermore, to be inline with Satcubes product portfolio and the market trend, the product should be compact and light weight to ensure high portability. From conceptualisation to detailed design, an agile prototyping approach was imple mented with additions of rapid prototyping, mainly with 3D-printers, which proved to be important. The design process progressed in iterative cycles which provided rapidly produced prototypes at the end of each cycle, this made sure the project moved in the right direction. Since the surfaced challenges largely were related to complex mechanisms with several constituent parts, iterative development of the in dividual components provided results at a smaller scale, from which improvements could be made to the product as a whole. With the inclusion of rapid prototyping during the final design phase, quick design choices could be made and this ensured the best possible outcome. The thesis presents a detailed account of the process, which includes the challenges faced and solutions adopted. The resulting auto-pointer prototype confirms the hy pothesis and demonstrates the feasibility of the two actuator concept. The final prototype is able to rotate the azimuth, polarisation and elevation with only two actuators. It does this by utilising a clutch mechanism between azimuth and polar isation which disengages after the antenna has been elevated enabling the azimuth to be rotated individually. However, it is important to notice that since the purpose of the prototype was to prove the clutch as a concept, further development of the auto-pointer is needed for a final product to emerge. However, the prototype pro vides a reliable foundation for future work in this area. Overall, the thesis highlights the importance of a systematic product development approach in tackling complex engineering problems.
Keywords: auto-pointer, GEO satellites, antenna alignment, product development, agile prototyping, rapid prototyping